Copolymers based on azidopentyl-2-oxazoline: Synthesis, characterization and LCST behavior. (October 2015) - Le Fer, Gaëlle; Amiel, Catherine; Volet, Gisèle
Graphical abstract: Highlights: Polymers based on 2-(5-azidopentyl)-2-oxazoline successfully synthesized by CROP. Kinetics and reactivity ratio were studied. A LCST behaviour was detected for the first time for these copolymers. Abstract: Reactive polymers based on 2-(5-azidopentyl)-2-oxazoline (N3 PentOx) were prepared. This N3 PentOx monomer should be used to create a platform for the design of polyoxazoline based polymers with original architecture or polymer drug conjugates. The poly(2-(5-azidopentyl)-2-oxazoline) were synthesized by cationic ring-opening polymerization (CROP). A kinetic study was performed to demonstrate a good control over the polymerization of this functional oxazoline monomer. The polymerization constant was comparable to those reported for 2-methyl-2-oxazoline (PMeOx). Well-defined poly(2-methyl-2-oxazoline- co -2-(5-azidopentyl)-2-oxazoline) with low dispersity were prepared and characterized by FTIR spectroscopy, NMR spectroscopy and size exclusion chromatography. The reactivity ratios ( r MeOx = 1.73 and r N 3 PentOx = 0.71 ) of each monomer were determined, indicating a slight compositional heterogeneity in the synthesized quasi-statistical copolymers. Although PMeOx is known to have no LCST, the copolymers with small amount of N3 PentOx presented a lower critical solution temperature (LCST) behavior depending on molecular weights and composition of the copolymers.